Changes in Seated Pulmonary Artery Pressure in Response to Titration of Heart Failure Medications During Ambulatory Monitoring - ZALAWADIYA, SANDIP K.; KIERNAN, MICHAEL; BORLAUG, BARRY A.; STEVENSON, LYNNE WARNER; DESAI, AKSHAY S.; BENNETT, MOSI; MULLENS, WILFRIED; HIIVALA, NICHOLAS J.; OWENS, MAX M.; KLEIN, LIVIU (Journal of cardiac failure, 2025)
•Examining the short-term responses of pulmonary artery pressure (PAP) after isolated titrations of heart failure (HF) medications is critical to the development of management algorithms that incorporate the recommended medications and target optimal PAP.•The seated mean pulmonary artery pressure (mPAP) responded to diuretic titrations independent of the underlying Left ventricular ejection fraction (LVEF). Our observations can be utilized in development of management algorithms for patient self-management.•Up-titration of angiotensin receptor neprilysin inhibitor (ARNI) was followed by a significant decline in mPAP and down-titration of mineralocorticoid receptor antagonist (MRA) was followed by a significant rise in the mPAP. Short-term trends in PAP seen with titration of ARNI and MRA can provide valuable insights to clinicians in ambulatory management of HF. Ambulatory hemodynamic monitoring (AHM) of heart failure (HF) using pulmonary artery pressure (PAP) is marked by frequent changes in HF medications. We are beginning to learn how medication titrations during AHM affect mean PAP (mPAP) measured in the seated position, which reflects most waking hours. We analyzed the 12-month data from the PROACTIVE-HF trial of the Cordella Cordella, Endotronix Inc, Naperville, Illinois, United States) PAP sensor system. Seated mPAP was examined in the 14-days before and after isolated changes in medications; only those medications with ≥10 titrations were analyzed. Dependent sample Wilcoxon-signed rank test was used to compare changes in mPAP with titrations. We analyzed 456 subjects (age: 64 years, females: 40%, Black: 18%, HF with reduced ejection fraction: 46%). Loop diuretics (LD) were up-titrated 176 times in 133 patients and down-titrated 113 times in 96 patients. Before LD up-titration, mPAP increased by 1.6 ± 1.0 mm Hg; afterwards, it decreased by 2.3 ± 1.0 mm Hg (P < 0.001), with most reduction occurring within 1 week. Down-titration of LD was followed by an increase of 1.8 ± 1.3 mm Hg (P = 0.004) over the next several days. Similar trends were observed across categories of ejection fraction (≤40% and >40%). Angiotensin receptor neprilysin inhibitor (ARNI) up-titration decreased mPAP by 1.8 ± 1.9 mm Hg (P = 0.042), whereas down-titration increased mPAP by 1.5 ± 1.4 (P = 0.094). Mineralocorticoid receptor antagonist (MRA) up-titration tended to decrease mPAP (1.6 ± 2.5 mm Hg, P = 0.286,) whereas down-titration was followed by a significant increase in mPAP of 3.2 ± 1.6 mm Hg (P = 0.001). The AHM platform using seated mPAP data provided valuable insights into its short-term responses to isolated changes in HF medications. The seated mPAP changed expectedly in response to the titration of LD, whereas the degree of response varied for ARNI and MRA. Ongoing investigation will further characterize the timing and variability of responses to inform algorithms for ambulatory management of PAP.